A novel method for ash analysis in wheat milling fractions by using laser-induced breakdown spectroscopy. (November 2017) - Sezer, Banu; Bilge, Gonca; Sanal, Turgay; Koksel, Hamit; Boyaci, Ismail Hakki
Abstract: Ash content is an important quality control parameter in milling industry. Measurement of ash content is routinely performed using standard ash analysis method in which the sample is burned at 500–600 °C for 5–6 h. However, this method is not convenient for industrial applications, and thus, rapid and reliable methods are needed to be developed. The aim of this study was to develop a new method for ash analysis to be used in wheat milling fractions by using laser induced breakdown spectroscopy (LIBS). LIBS is an optic based multi-elemental, spectroscopic method which can analyze high number of samples in a considerably short time. In the study, wheat flour, whole wheat meal and semolina samples with different ash contents were analyzed using LIBS, and the spectra were evaluated with partial least squares (PLS) method. The results were correlated with the ones taken from standard ash analysis method. Calibration graph showed good linearity with the ash content between 0.48 and 2.44%, and 0.997 coefficient of determination (R 2 ). Limit of detection for ash analysis was calculated as 0.11%. The results indicated that LIBS is a promising and reliable method with high sensitivity for routine ash analysis in milling industry. Highlights: The ash content of wheat milling fractions were measured by using LIBS. Mineral contents of wheat flour, whole wheat meal and semolina were measured by LIBS. Multi-variate analysis was used to quantify the ash content of wheat flour, whole wheat meal and semolina. LIBS is a reliable, rapid and in-situ method for determination of ash content.